Whitecap features induced by submarine sand waves in stereo optical imagery. Issue 9 (13th September 2015) - Zhang, Huaguo; Lou, Xiulin; Li, Yan; Shi, Aiqin; Li, Dongling; Fu, Bin
Abstract Under high wind speed conditions, waves break on the sea surface producing whitecaps, which can be recorded in optical satellite images. However, the breaking of waves is also influenced by submarine topography. In this study, we investigate the whitecap features induced by submarine sand waves using optical stereo images. We determine the whitecap coverage in images, and estimate the probabilities of wave breaking. The observed and estimated results are in agreement with some previous investigation results. A physical model is used to discuss the mechanisms of wave breaking along sand wave crests. The physical model is able to qualitatively explain the differences between the observed whitecap coverage and the estimated probability of wave breaking between the sand wave area (SWA) and the background area (BGA). Further analysis shows that the periodic sand wave system may play the role of a frequency‐control device, and may result in more broken waves in the SWA than in the BGA. This study demonstrates that it is possible to observe submarine topography under high‐wind conditions by using whitecap features.